Profiling delay and throughput characteristics of interactive multimedia traffic over WLANs using OPNET - Abdul Latif, Suhaimi; Rashid, M. A.; Alam, F. (2007)
Performance statistics of WLANs in published literatures are limited only to homogeneous traffic. However, mixed traffic scenario is prevailing in WLANs. This paper is an effort to characterize WLANs behaviour in transmitting mixed traffic. OPNET was used to simulate a typical WLANs scenario. It was found that tuning the CFP and superframe size dynamically will achieve better end-to-end delay and throughput profiles.